17. yüzyılda yapılmış mensur şehname tercümesi 120a - 159b - Aktaş, Erhan (My University, 2005)
Bir bölümü üzerinde çalışılan eser, İstanbul Üniversitesi Merkez Kütüphanesi'nde 6131 demirbaş numarasıyla kayıtlıdır. Üç cilt olup tamamı 1778 varaktır. Her sayfasında 25 satır bulunan bu eserde minyatürlere de yer verilmiştir. Üzerinde çalışma yapılan birinci cildin boyu 39, eni 24,5 ve kalınlığı 7,5 cm'dir. Kelime kelime bir tercüme niteliği taşımayan bu eser hicrî 1187, milâdî 1773 tarihinde tamamlanmıştır. Bu tez yazmanın 120a-159b varaklarını kapsamaktadır. Eserin 01b-40b varakları Sadettin Şahin, 41a-80b varakları Sema Demirel Şahin tarafından olarak hazırlanmıştır. Bu tezi hazırlamaktaki amaç Şehnâme'nin bu mensur tercümesini tanıtmaktır. Tez giriş, metin ve sözlük olmak üzere üç bölümden oluşmaktadır. Tezin giriş kısmında Firdevsî, Şehnâme, Şehnâme çevirileri ve üzerinde çalışma yapılan yazmayla ilgili bilgiler verilmiştir. Metin kısmında sayfa ve satır numaraları belirtilmiştir. Metin günümüz noktalama işaretlerine göre düzenlenmiş, metnin gerekli yerlerinde paragraflar yapılmıştır. Yapılan bu düzenlemeyle eserden faydalanmanın daha kolay bir hâle getirilmesi amaçlanmıştır. Sözlük ise hem alfabetik hem de kök esasına dayalı bir sözlüktür. Madde başı yapılan kelimelerin altına o kelimeyle ilgili ara madde, deyim ve birleşikler sıralanmış, madde başı veya ara maddelerin ikinci, üçüncü unsur olarak geçtiği maddelere (þ) işaretiyle göndermeler yapılmıştır.

The book that we have worked on, is registered under fixture number 6131 at the Central Library of İstanbul University. It's composed of 3 volumes with total pages of 1778. Miniatures also have been given place in the book with each page designed 25 lines. The length of the first volume on which work is being carried on, is 39 cm, width is 24.5 cm and thickness is based 7.5 cm. The work that doesn't carry the characteristic of a translation word by word was completed on 1187 (date based Hegira) or 1773 (date based on birth of Christ/ Christian era). The thesis covers pages 120a - 159b of the manuscript. Pages 01b - 40b and pages 41a - 80b had been prepared as a master's thesis by Mr. Sadettin Şahin and Ms. Sema Demirel Şahin respectively. The reason to prepare this thesis is to introduce the translation of Şehnâme in prose. The thesis is composed of three sections which are the introduction, the text and the dictionary. The information about Firdevsi, Şehnâme, Şehnâme translations and manuscript on which work is carried on is given at the introduction section of thesis. The text shows the pages and line numbers. It has been designed according to up to date punctuation marks. Paragraphs have been created at the necessary parts. In this way, it has been aimed to get benefit of the work more easily. The dictionary is based on both alphabetic and root principles. The wording accepted as the beginning (main) item has down below the intermediary item, expression and composed wording related to that word. The items identified as second, third factors of the main or intermediary items have been referred with marking (þ).
Keywords: Edebiyat; İran edebiyatı; İran Edebiyatı_Şehname